Comparative Analysis of Financial Performance of Family Companies and Non-Family Companies - Septianasari, Ratri; Gunarto, Muji (International Journal of Finance Research, 2024)
This study aims to analyze and compare the financial performance of family and non-family companies. The objects in this study are banking sub-sector companies and state-owned companies listed on the Indonesia Stock Exchange in 2023. This type of research is descriptive quantitative. The number of samples taken in this study were 37 companies and 11 non-family companies. A purposive sampling technique was used. This study indicates differences in profitability, activity, and liquidity ratios between family and non-family companies. No difference exists in leverage ratio, capital structure, and stock price between family and non-family companies. This research is expected to contribute to and refer to further research comparing the financial performance of family and non-family companies.